Integrating Adjuvant Analgesics into Perioperative Pain Practice: Results from an Academic Medical Center. Issue 1 (1st April 2019) - Chin, Kuo-Kai; Carroll, Ian; Desai, Karishma; Asch, Steven; Seto, Tina; McDonald, Kathryn M; Curtin, Catherine; Hernandez-Boussard, Tina
Abstract: Background: Opioid-sparing postoperative pain management therapies are important considering the opioid epidemic. Total knee arthroplasty (TKA) is a common and painful procedure accounting for a large number of opioid prescriptions. Adjuvant analgesics, nonopioid drugs with primary indications other than pain, have shown beneficial pain management and opioid-sparing effects following TKA in clinical trials. We evaluated the adjuvant analgesic gabapentin for its usage patterns and its effects on opioid use, pain, and readmissions. Methods: This retrospective, observational study included 4, 046 patients who received primary TKA between 2009 and 2017 using electronic health records from an academic tertiary care medical institute. Descriptive statistics and multivariate modeling were used to estimate associations between inpatient gabapentin use and adverse pain outcomes as well as inpatient oral morphine equivalents per day (OME). Results: Overall, there was an 8.72% annual increase in gabapentin use ( P  < 0.001). Modeled estimates suggest that gabapentin is associated with a significant decrease in opioid consumption (estimate = 0.63, 95% confidence interval = 0.49–0.82, P  < 0.001) when controlling for patient characteristics. Patients receiving gabapentin had similar discharge pain scores, follow-up pain scores, and 30-day unplanned readmission rates compared with patients receiving no adjuvant analgesics ( P  > 0.05). Conclusions: When assessed in a real-world setting over a large cohort of TKA patients, gabapentin is an effective pain management therapy that is associated with reduced opioid consumption—a national priority in this time of opioid crisis—while maintaining the same quality of pain management.